Measurement of $CP$ asymmetry in $D^0 → K^- K^+$ and $D^0 → π^- π^+$ decays - collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; Cartelle, P; et al. (2014)
Time-integrated $CP$ asymmetries in $D^0$ decays to the final states $K^- K^+$ and $π^- π^+$ are measured using proton-proton collisions corresponding to $3\mathrm{\,fb}^{-1}$ of integrated luminosity collected at centre-of-mass energies of $7\mathrm{\,Te\kern -0.1em V}$ and $8\mathrm{\,Te\kern -0.1em V}$. The $D^0$ mesons are produced in semileptonic $b$-hadron decays, where the charge of the accompanying muon is used to determine the initial flavour of the charm meson. The difference in $CP$ asymmetries between the two final states is measured to be \begin{align} Δ A_{CP} = A_{CP}(K^-K^+)-A_{CP}(π^-π^+) = (+0.14 ± 0.16\mathrm{\,(stat)} ± 0.08\mathrm{\,(syst)})% \ . \nonumber \end{align} A measurement of $A_{CP}(K^-K^+)$ is obtained assuming negligible $CP$ violation in charm mixing and in Cabibbo-favoured $D$ decays. It is found to be \begin{align} A_{CP}(K^-K^+) = (-0.06 ± 0.15\mathrm{\,(stat)} ± 0.10\mathrm{\,(syst)}) % \ ,\nonumber \end{align} where the correlation coefficient between $Δ A_{CP}$ and $A_{CP}(K^-K^+)$ is $ρ=0.28$. By combining these results, the $CP$ asymmetry in the $D^0→π^-π^+$ channel is $A_{CP}(π^-π^+)=(-0.20±0.19\mathrm{\,(stat)}±0.10\mathrm{\,(syst)})%$.